Blockade of growth hormone receptor signaling by using pegvisomant: A functional therapeutic strategy in hepatocellular carcinoma - Kaseb, Ahmed O.; Haque, Abedul; Vishwamitra, Deeksha; Hassan, Manal M.; Xiao, Lianchun; George, Bhawana; Sahu, Vishal; Mohamed, Yehia I.; Carmagnani Pestana, Roberto; Lombardo, Jamie Lynne; Avritscher, Rony; Yao, James C.; et al. (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is an aggressive neoplasm with poor clinical outcome because most patients present at an advanced stage, at which point curative surgical options, such as tumor excision or liver transplantation, are not feasible. Therefore, the majority of HCC patients require systemic therapy. Nonetheless, the currently approved systemic therapies have limited effects, particularly in patients with advanced and resistant disease. Hence, there is a critical need to identify new molecular targets and effective systemic therapies to improve HCC outcome. The liver is a major target of the growth hormone receptor (GHR) signaling, and accumulating evidence suggests that GHR signaling plays an important role in HCC pathogenesis. We tested the hypothesis that GHR could represent a potential therapeutic target in this aggressive neoplasm. We measured GH levels in 767 HCC patients and 200 healthy controls, and then carried out clinicopathological correlation analyses. Moreover, specific inhibition of GHR was performed in vitro using siRNA and pegvisomant (a small peptide that blocks GHR signaling and is currently approved by the FDA to treat acromegaly) and in vivo, also using pegvisomant. GH was significantly elevated in 49.5% of HCC patients, and these patients had a more aggressive disease and poorer clinical outcome (P<0.0001). Blockade of GHR signaling with siRNA or pegvisomant induced substantial inhibitory cellular effects in vitro. In addition, pegvisomant potentiated the effects of sorafenib (P<0.01) and overcame sorafenib resistance (P<0.0001) in vivo. Mechanistically, pegvisomant decreased the phosphorylation of GHR downstream survival proteins including JAK2, STAT3, STAT5, IRS-1, AKT, ERK, and IGF-IR. In two patients with advanced-stage HCC and high GH who developed sorafenib resistance, pegvisomant caused tumor stability. Our data show that GHR signaling represents a novel “druggable” target, and pegvisomant may function as an effective systemic therapy in HCC. Our findings could also lead to testing GHR inhibition in other aggressive cancers.